Utilising waste products from Kwinana industries to manufacture low specification geopolymer concrete - Slabbert, Michael Charles (Curtin University, 2008)
One technology that makes concrete without cement and does not have the associated carbon footprint is geopolymer concrete. This technology utilizes waste fly ash from power stations and mixes it with activating chemicals to form a binder with similar or better properties than cement. Not only does this technology directly reduce carbon emissions by replacing cement it also utilizes the waste bi-product from power stations and prevents it from going to landfill. Concrete is composed of coarse aggregates, sand and cementitious paste. It seemed possible to make geopolymer concrete from 100% waste. The aggregates would come from recycled concrete and hard brittle bottom ash from power stations, the sand would come from foundries and the fly ash binder would also come from the same power station as the bottom ash. All of these materials are waste and would all be dumped in landfill. Where would one find all these waste materials in one place? The industrial suburb of Kwinana outside Perth is home to a large number of industries producing all these wastes. To find products that have a specification that these materials would suit was a material with a relatively low specification, one such specification is the concrete masonry units’ specification. For this to be adopted the mix design would then have to be altered to a drier type mix without any slump. As recycling facilities do not make a range of products it was decided to crush the aggregates in the laboratory specifically for this research and to blend all the waste materials. Numerous combinations were blended, analysed and assessed to establish which blends would best suit the aims and scope of this research. Eventually three blends were selected that encompassed all the waste products.To find the right mix design proved challenging as these masonry products generally require a mix to have zero slump. It was decided to test across all the known and analysed water to geopolymer solids ratios for each of the mixes and establish the best mix based on compressive strength, workability and slump A known mix design based on research into low calcium Class F geopolymer concrete, developed at Curtin University using natural aggregates, was applied to these selected recycled waste mix designs. The benefit was to be able to compare the results of this research to a known result. Flash setting, an unknown phenomenon in geopolymer concrete, did occur in the low water mixes, but in spite of this, geopolymer concrete was successfully manufactured. The compressive strengths were substantially lower than those of the design mix and more research is required in this regard, however an indirect relationship was observed between the amount of bottom ash and the compressive strength. The high degree of LOI (loss of ignition) in both ashes, porosity of recycled aggregates, angularity, degree of fineness of the fines and flash setting are all possible factors influencing the properties of the geopolymer concrete. More research is recommended in a number of these areas to be able to understand and develop this technology further in order to make this a practical and robust technology in the quest to find solutions to our warming planet and our changing climate.